Thermodynamic analysis of a novel pumped thermal energy storage system utilizing ambient thermal energy and LNG cold energy. (15th September 2017) - Wang, Guan-Bang; Zhang, Xin-Rong
Highlights: Ambient thermal energy and LNG cold energy are used as the heat source and sink. Higher round trip efficiency than other energy storage technology is obtained. Energy and exergy analysis are conducted with a steady-state thermodynamic model. Genetic Algorithm is employed for optimization of some system parameters. Sensitivity of system performance to different parameters is analyzed. Abstract: Pumped thermal energy storage (PTES) has become a hot topic on large scale energy storage technology because of the independence on geological conditions and fossil fuels. However, few of the PTES systems have higher round trip efficiencies compared with that of pumped hydro storage except for systems utilizing external heat sources. Furthermore, the used external heat sources are not available everywhere and much additional cost is required for the system integration. As an accessible and cheap heat source, ambient thermal energy is employed in the newly proposed PTES system. LNG (liquid natural gas) cold energy is also used as the heat sink based on possible combination with the natural gas distribution system in the practical operation. The charge process is based on transcritical CO2 heat pump cycle, while cascade design of transcritical CO2 Rankine cycle and subcritical NH3 Rankine cycle is employed in the discharge process. A thermodynamic model is established for energy and exergy analysis as well as the system evaluation. The analysis and evaluation of the optimized baseline case obtained by Genetic Algorithm are then carried out. In addition, the sensitivity of system performance to different variable parameters is also analyzed. Based on the analysis of optimized baseline case, the round trip efficiency can reach 139%. If for 1 MW net power output, both of the mass flow rates of CO2 and NH3 are 7.4 kg/s with LNG mass flow rate of 14.8 kg/s. Because of much higher round trip efficiency compared with other large scale energy storage systems, the proposed system is promising for future development and applications.